SPATIAL CLUSTERIZATION OF FISHING AREA IN BULU WATERS, TUBAN REGENCY - Sari, Wahida Kartika; Kusuma, Andre Laila; Harlyan, Ledhyane Ika; Sambah, Abu Bakar; Adhihapsari, Wirastika (Directorate of Research and Community Service (DRPM), 2023)
The various characteristics of catches and fishing gear provide distinct advantages for fishermen, but these characteristics can cause other problems, namely pressure on stock availability caused by an increase in the number of catches and the use of various types of fishing gear and the efficiency provided. There needs to be good management to handle this. The purpose of this research is to find out the clusterization (grouping) of fishing areas based on the catch and the type of fishing gear in which the results of this study are used as a reference in sustainable fisheries management. This research uses descriptive methods and case studies at PPP Bulu. The analytical method used is the Shannon-Wienner index of diversity (S-W,H'), Margalef richness (R') and clusterization. Clusterization was analyzed using the Hierachical Cluster Analysis (HCA) method to obtain the Euclidean distance. The results showed that the value of diversity has a range of 0-2 and the value of wealth has a range of 1-10. The results of the clusterization show that there are 3 clusters of fishing areas formed based on the catch, while no clusters of fishing areas are formed based on the type of fishing gear operated.